STUDIES ON CULTURED CONDITIONS OF MARINE CHROMATIUM BUDERI TRUPER AND JANNASCH 1968 - DHEVENDARAN, K (Fishery Technology, 2017)
Photosynthetic characteristics of a purple sulfur bacterium, Chromataun buderi, cultured under different ranges of pH, temperature, light intensities and ammonium chloride concentrations were examined. Maximum bacteriochlorophyll a synthesis was observed at pH 6.5 whereas the optimum growth was at pH 8.0. In general, highertemperature tended to inhibit the chlorophyll a synthesis and growth. 30Â°C is the optimum temperature both for chlorophyll a synthesis and growth. At 25 tIE m â€”25 the bacteriochlorophyll a content and growth attained maximum level. The response to this low light intensity is an adaptation that ensure a high photosynthetic rate for the purple sulfur bacterium that usually occurs in dimly lit environment. Besides these,ammonium chloride at low concentration enhances both chlorophyll a sy thesis and growth. Above 0.5 % of it cause the nitrogen-chlorosis and also retard the growth of the bacterium. Possible chemical and structural mechanisms involved are discussed.